New Evidence for the History of the Abydene Nobility from the Early First Intermediate Period. Part II - Bogdanov, Ivan V. (Chronique d’Égypte, 2023)
Abstract The aim of the paper is to reconstruct a line of seven generations of the Abydene nobility whose ancestor was jww I, a vizier under King ppj I mrj-rʿ. The senior members of this family were related to Queen ʿnḫ-n=s-ppj III, the mother of King nfr-kA-rʿ II. Finally, the identification of the queens with the name ʿnḫ-n=s-ppj in various sources is discussed.